DESIGNING FOR THE SENSES: MULTISENSORY APPROACHES IN THERAPEUTIC CLINICAL SPACES - Malhotra, Arushi; Abrol, Meeru (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Spatial design significantly influences interactions with the built environment, engaging senses through visual, auditory, and tactile stimuli. However, in therapeutic clinical settings, the sensory experience is often overlooked in favor of aesthetic considerations, limiting the understanding of user responses to spatial cues. This study investigates the role and impact of multisensory design on user responses in therapeutic clinical environments. By analyzing design parameters such as lighting, acoustics, materials, and textures, the research aims to establish a framework for creating therapeutic clinical spaces that prioritize multisensory stimulation. Through case studies, interviews, and surveys, the study assesses user perceptions and psychological responses to different sensory stimuli in clinical settings. The findings indicate a preference for environments that engage multiple senses, with factors such as layout, color tones, forms, lighting, and finishes playing crucial roles in shaping user experiences. The proposed framework offers practical guidance for designers and architects, emphasizing the importance of sensory design in enhancing interactions between users and clinical environments, ultimately contributing to a more holistic and immersive therapeutic experience.